Mapping the peripheral nervous system in the whole mouse via compressed sensing tractography. (8th June 2021) - Garrett, Aliesha; Rakhilin, Nikolai; Wang, Nian; McKey, Jennifer; Cofer, Gary; Anderson, Robert BJ; Capel, Blanche; Johnson, G Allan; Shen, Xiling
Abstract: Objective. The peripheral nervous system (PNS) connects the central nervous system with the rest of the body to regulate many physiological functions and is therapeutically targeted to treat diseases such as epilepsy, depression, intestinal dysmotility, chronic pain, and more. However, we still lack understanding of PNS innervation in most organs because the large span, diffuse nature, and small terminal nerve bundle fibers have precluded whole-organism, high resolution mapping of the PNS. We sought to produce a comprehensive peripheral nerve atlas for use in future interrogation of neural circuitry and selection of targets for neuromodulation. Approach. We used diffusion tensor magnetic resonance imaging (DT-MRI) with high-speed compressed sensing to generate a tractogram of the whole mouse PNS. The tractography generated from the DT-MRI data is validated using lightsheet microscopy on optically cleared, antibody stained tissue. Main results. Herein we demonstrate the first comprehensive PNS tractography in a whole mouse. Using this technique, we scanned the whole mouse in 28 h and mapped PNS innervation and fiber network in multiple organs including heart, lung, liver, kidneys, stomach, intestines, and bladder at 70 µ m resolution. This whole-body PNS tractography map has provided unparalleled information; for example, it delineates the innervation along the gastrointestinal tract by multiple sacral levels and by the vagal nerves. The map enabled a quantitative tractogram that revealed relative innervation of the major organs by each vertebral foramen as well as the vagus nerve. Significance. This novel high-resolution nerve atlas provides a potential roadmap for future neuromodulation therapies and other investigations into the neural circuits which drive homeostasis and disease throughout the body.